ChemInform Abstract: New Lanthanide Mixed‐Valent Vanadium(III/IV) Oxosilicates, Ln4V5‐xZnxSi4O22 (Ln: La, Ce, Pr, and Nd), Crystallizing in a Quasi Two‐Dimensional Rutile‐Based Structure. Issue 18 (April 2016) - Abeysinghe, Dileka; Smith, Mark D.; Yeon, Jeongho; Morrison, Gregory; zur Loye, Hans‐Conrad
Abstract: Single crystals of the title compounds are grown via a molten flux method employing a 1:2:2 molar mixture of Ln2 O3, V2 O5, and Zn in a eutectic CsCl/NaCl mixture (evacuated silica tubes acting as Si source, 1000 °C, 24 h).